Potential cost-effectiveness of schistosomiasis treatment for reducing HIV transmission in Africa--the case of Zimbabwean women. - Martial L Ndeffo Mbah; Eric M Poolman; Katherine E Atkins; Evan W Orenstein; Lauren Ancel Meyers; Jeffrey P Townsend; Alison P Galvani (Public Library of Science (PLoS), 2013)
Epidemiological data from Zimbabwe suggests that genital infection with Schistosoma haematobium may increase the risk of HIV infection in young women. Therefore, the treatment of Schistosoma haematobium with praziquantel could be a potential strategy for reducing HIV infection. Here we assess the potential cost-effectiveness of praziquantel as a novel intervention strategy against HIV infection.We developed a mathematical model of female genital schistosomiasis (FGS) and HIV infections in Zimbabwe that we fitted to cross-sectional data of FGS and HIV prevalence of 1999. We validated our epidemic projections using antenatal clinic data on HIV prevalence. We simulated annual praziquantel administration to school-age children. We then used these model predictions to perform a cost-effectiveness analysis of annual administration of praziquantel as a potential measure to reduce the burden of HIV in sub-Saharan Africa.We showed that for a variation of efficacy between 30-70% of mass praziquantel administration for reducing the enhanced risk of HIV transmission per sexual act due to FGS, annual administration of praziquantel to school-age children in Zimbabwe could result in net savings of US$16-101 million compared with no mass treatment of schistosomiasis over a ten-year period. For a variation in efficacy between 30-70% of mass praziquantel administration for reducing the acquisition of FGS, annual administration of praziquantel to school-age children could result in net savings of US$36-92 million over a ten-year period.In addition to reducing schistosomiasis burden, mass praziquantel administration may be a highly cost-effective way of reducing HIV infections in sub-Saharan Africa. Program costs per case of HIV averted are similar to, and under some conditions much better than, other interventions that are currently implemented in Africa to reduce HIV transmission. As a cost-saving strategy, mass praziquantel administration should be prioritized over other less cost-effective public health interventions.